The Influence of Job Stress, Workload, and Work-Life Balance on Employee Performance with Job Satisfaction as a Mediator Among Private Employees in Tangerang City - Manuel, Andre; Priyowidodo, Agustinus (Fakultas Bisnis, 2025)
This study aims to analyze the influence of job stress, workload, and work-life balance on employee performance, with job satisfaction as a mediating variable, in private companies located in Tangerang City. The study is motivated by the importance of addressing job stress, reducing excessive workload, and recognizing the significance of balancing professional and personal life in order to enhance employee performance. Private sector organizations in urban centers like Tangerang are increasingly facing challenges in maintaining workforce productivity due to heightened pressure, demanding workloads, and blurred boundaries between work and personal life. These factors can lead to diminished job satisfaction and ultimately decreased employee performance. Understanding how these factors interrelate, particularly the role of job satisfaction as a mediating variable, can help organizations implement more effective human resource strategies and performance improvement initiatives. A quantitative approach was employed in this research, with data collected via an online questionnaire distributed through Google Forms. The sample was selected using a convenience sampling method, targeting employees with a minimum of one year of work experience. The data were analyzed using SmartPLS software and Structural Equation Modeling (SEM) to examine relationships and mediating effects among variables. The findings show that job stress, workload, and work-life balance significantly affect employee performance. Furthermore, job satisfaction mediates the influence of job stress and workload on employee performance, although it does not mediate the relationship between work-life balance and performance. The study provides practical recommendations for companies to enhance job satisfaction and support employees' work-life balance as strategies to optimize performance.